The clinical application of critical flicker fusion frequency in demyelinating optic neuritis - Junxia Fu; Yongping Wang; Shaoying Tan; Guangcan Xu; Huanfen Zhou; Quangang Xu; Shihui Wei (Advances in Ophthalmology Practice and Research, 2021)
Purpose: To investigate the application of critical flicker fusion frequency (CFF) in demyelinating optic neuritis (DON). Methods: A cross-sectional study. A total of 127 eyes in 69 DON patients and 63 eyes in 33 healthy control (HC) groups were included between January 2021 to September 2021 from Department of Ophthalmology, PLA General Hospital. Patients underwent best-corrected visual acuity (BCVA), visual field, optical coherence tomography (OCT), flash visual evoked potential (F-VEP), and CFF examinations. The affected eyes were divided into aquaporins 4 (AQP4-), myelin oligodendrocyte glycoprotein (MOG-), and double negative DON according to serum antibody; mild, moderate, severe degree visual impairment according to BCVA ≥ 0.5, 0.1-0.5, < 0.1; and 4 groups: < 1, 1 ∼< 3, 3 ∼ < 6 and > 6 months according to time interval from onset to CFF examination. One-way ANOVA was used to perform above subgroup analysis. The correlations between CFF and F-VEP peak time, peak value, BCVA and mean visual filed defect (MD) were analyzed in order via Pearson correlation analysis. Results: he trichromatic values of red, green, and yellow in DON affected eyes were 21.83 ± 9.03, 23.66 ± 10.21, 24.09 ± 10.77 Hz, respectively, which was significantly reduced compared with the HC group (t = -14.82, -14.22, -14.00; P < 0.001). The subgroup analysis showed no significant difference between different antibody subtypes (P = 0.914 <0.848 <0.604), whereas, a significant decrease of CFF trichromatic value was found in severe visual acuity impairment group (P < 0.001). There was a significant difference in CFF- trichromatic values at different time points (P < 0.001), to be specific, CFF fluctuated under 20Hz within 3 months after onset and tended to be stable around 24-28Hz. Correlation analysis showed that the peak time of F-VEP (r = -0.486, -0.515, -0.526; P < 0.001), BVCA (r = -0.640, -0.659, -0.642; P < 0.001), were negatively correlated with CFF trichromatic values, MD and CFF were positively correlated (r = 0.486, 0.453, 0.476; P = 0.003, 0.006, 0.004). Conclusions: A significant decrease of CFF value was found in DON-affected eyes, and it has a good correlation with BCVA, MD and latency of F-VEP, and can better reflect the impairment of visual function